PHYSICOCHEMICAL, ORGANOLEPTIC AND BUSINESS FEASIBILITY ANALYSIS OF CHICKEN NUGGETS WITH VARYING DOSAGES OF MORINGA LEAVES AND TAPIOCA FLOUR - Costa W.Y.; Mbapa F.; Sarjono W. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
This study explores the use of Moringa leaves and tapioca flour as additives in chicken nuggets, a popular processed chicken meat product. Moringa leaves are known for their high nutritional content, including vitamins, minerals, and antioxidants. The research aims to determine the optimal dosages of Moringa leaves and tapioca flour for chicken nugget production, providing guidance for producers to enhance product formulations and nutritional value. The study investigates how variations in the doses of Moringa leaves and tapioca flour impact the physicochemical and organoleptic properties of chicken nuggets. An experimental design involving two factors (Moringa leaves and tapioca flour) with multiple levels is utilized. Each treatment combination is repeated to obtain reliable results. The findings indicate significant interactions between the doses of Moringa leaves and tapioca flour, particularly related to water content. The addition of 300g tapioca flour and 200g Moringa leaves resulted in the lowest water content compared to other dose combinations. However, there was no significant interaction observed on ash content, although higher doses of Moringa leaves and tapioca flour tended to increase the ash content in the chicken nuggets. Crude protein levels showed an interaction effect, with the addition of 100g Moringa leaves and increased tapioca flour contributing positively to the crude protein content. Additional doses of Moringa leaves and tapioca flour affected the crude fat content, with the addition of 100g Moringa leaves and increased tapioca flour resulting in increased crude fat. However, higher doses in specific combinations led to varied effects on crude fat content. The addition of Moringa leaves and tapioca flour influenced the crude fiber content in chicken nuggets. Within a certain range, the addition of Moringa leaves positively increased the crude fiber content, while higher doses of tapioca flour also contributed to increased crude fiber. Overall, this research provides insights into the effects of Moringa leaves and tapioca flour on the physicochemical properties and organoleptic qualities of chicken nuggets. The findings offer valuable information for the development of more efficient product formulations with enhanced nutritional value.